EFEK PEMBERIAN TUNGGAL PINANG MUDA DOSIS TINGGI PADA HEPAR TIKUS (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2018)
Introduction : Raw betel nuts juice is a traditional herbal supplement in Jambi that is consumed for stamina booster. According to previous study, raw betel nut has median lethal dose >15.000 mg/kg weight. Hepatotoxicity is often caused by herbal supplement in high dose. Purpose : This study is to determine the effect of single high dose of raw betel nut on rat’s liver. Methods : this experimental study used rats strain sprague dawle, health and active, age 2-3 month, weight 150-200 gram. There are 6 rats in each groups. Experimental group receveid raw betel nut juice single dose 20.000gram/kg weights and control group received aquadest. Observation of mortality rate during 7 days. Termination of rats were done on 8th days. Histopathology used Hematoxilin Eosin stain. Results : One rats (16,6%) was found died on 24 hours after treatment with raw betel nut Histopatholgy examination showed portal inflamation, hepatocellular cholestasis, and steatosis in group of raw betel nut. Conclusions : raw betel nut in single high dose could cause liver damages. Keywords : betel nuts, histopatholohy, liver